Europe and Central Asia Economic Update, Spring 2022 : War in the Region - World Bank (Washington, DC: World Bank, 2022)
In February 2022, the world was shocked by the Russian Federation’s invasion of Ukraine. The war is having a devastating impact on human life and causing economic destruction in both countries, and will lead to significant economic losses in the Europe and Central Asia (ECA) region and the rest of the world. It comes at a particularly vulnerable time for ECA as its economic recovery was expected to be held back by scarring from the pandemic and lingering structural weaknesses. The economic impact of the conflict has reverberated through multiple channels, including commodity and financial markets, trade and migration links, and the damaging impact on confidence. Moreover, the war has added to mounting concerns about a sharp global slowdown, surging inflation and debt, and a spike in poverty levels. Neighboring ECA countries are likely to suffer considerable economic damage because of their strong trade, financial, and migration links with Russia and Ukraine. The war is also causing a destabilizing wave of refugees, financial stresses in vulnerable countries, runaway inflation expectations, and food insecurity. A protracted conflict could further heighten policy uncertainty and fragment critical trade and investment networks.